A Flexible, Extremely Sterically Demanding Triazenide Ligand: Synthesis and Coordination Chemistry. Issue 11 (31st May 2019) - Gyton, Matthew R.; Bhadbhade, Mohan; Cole, Marcus L.
Abstract : Seeking to further the investigation of extremely sterically congested main group metals, the synthesis of a new oligoaryl triazene (Dipp*2 N3 H) is reported. This was accessed by diazotization of Dipp*NH2 to access both Dipp*I and Dipp*N3 in high yield and with scalable preparations. These compounds are used as precursors to Dipp*2 N3 H, via a magnesium aryl, due to the difficulties in obtaining pure triazene via an aryl‐lithium species. Deprotonation of the triazene with both potassium and thallium tert ‐butoxides gives the respective metal triazenides in high yield. The solid‐state structures of these complexes have been determined and three high hapticity metal arene‐π interactions, which sterically shield the metal centers, were observed in each case; spectroscopic C 2 v symmetry suggests these interactions are fluxional in solution. The variability of these interactions in the solid state as well as the changes in calculated steric demand of the ligand between metals point to an adaptive, flexible coordination mode. Abstract :